BANK BRI KC SURABAYA KERTAJAYA: MITRA STRATEGIS UNTUK UMKM DAN INDIVIDU - Ida Ayu Nuh Kartini; Kharin Dinda Aisyah; Johana Rizky Widyastuti; Jessicka Amelia Joyta; Fitra Aoelintiano Nico Victorian (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
In the post-pandemic economic landscape, the banking industry faces a dual challenge: accelerating digital transformation while maintaining inclusivity for the unbanked sector. This study investigates the strategic role of Bank BRI Branch Office (KC) Surabaya Kertajaya in empowering Micro, Small, and Medium Enterprises (MSMEs) and individuals within the Surabaya ecosystem, specifically at Pasar Pucang Anom. Adopting a descriptive qualitative approach with simulated field observations and in-depth interviews, this research explores the implementation of the "Hybrid Bank" model, a synergy between digital capabilities and human presence. The findings reveal that the "Mantri" plays a pivotal role in mitigating information asymmetry through relationship banking grounded in social capital (silaturahmi). Furthermore, the distribution of People's Business Credit (KUR) with a 6% interest rate has effectively displaced informal predatory lenders. The adoption of digital tools like BRImo and QRIS is driven by perceived usefulness and trust, facilitated by the physical presence of the bank. This research concludes that the "High Tech - High Touch" strategy is essential for sustainable financial inclusion in emerging urban economies.